2016
DOI: 10.1007/s12665-016-6146-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemical characteristics of interstitial water and overlying water in the lacustrine environment

Abstract: This research was conducted in the lacustrine environment of Lake Wigry, one of the largest and deepest lakes in Poland. The main objective was to determine the relationship between the chemical composition of interstitial water, overlying water and bottom sediment in the different sedimentation conditions. Therefore, seven research positions were selected, taking into account different zones of lake and lithological type of deposits. Overlying water samples taken from zones with carbonate type of sediment (la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The terrigenous material, entering the reservoir due to the destruction of rocks and abrasions of shores, and transported with water ow, plays an important role in the genesis of pore water. As was shown earlier, the pore water chemistry is greatly in uenced by the chemical and mineralogical composition of bottom sediments [36].…”
Section: Sediments Of Reservoirmentioning
confidence: 68%
“…The terrigenous material, entering the reservoir due to the destruction of rocks and abrasions of shores, and transported with water ow, plays an important role in the genesis of pore water. As was shown earlier, the pore water chemistry is greatly in uenced by the chemical and mineralogical composition of bottom sediments [36].…”
Section: Sediments Of Reservoirmentioning
confidence: 68%
“…For example, calcium carbonate, which makes up lacustrine chalk, is partly precipitated with the participation of Charophyta (a group of algae), which leads to the formation of calcite tubes of even more than 1 cm in length, and it was found that those tubes are made of almost pure CaCO 3 [98]. Moreover, research on pore water mineralization of Wigry Lake sediments has revealed that it is relatively low in the case of lacustrine chalk (544.5 mg/L) when compared to other types of deposits (e.g., carbonate gyttja-717.7 mg/L; fluvial-lacustrine sediment-1670.9 mg/L) [120]. Con-sequently, apart from lacustrine chalk, clastic sediment, as the most coarse-grained, is also the least enriched with metals.…”
Section: Resultsmentioning
confidence: 99%
“…The pore water chemistry is greatly influenced by the chemical composition of bottom sediments. It was earlier shown that pore water contained in sediments have higher CaCO 3 (> 90%) contents, demonstrated pH values ranging between 7.7 and 8.2, relatively low TDS values and represented HCO 3 –Ca, HCO 3 –Ca–Mg or HCO 3 –SO 4 –Ca–Mg hydrochemical water types 36 .…”
Section: Discussionmentioning
confidence: 95%